Long-term outcomes of (Gore) fistula plug versus ligation of intersphincteric fistula tract for anal fistula - Alhaddad,Abdullah (2018)
ABSTRACT Background: The surgical treatment of anal fistula is complex due to the possibility of fecal incontinence. Fistulotomy and cutting Setons have the same incidence of fecal incontinence depending on the complexity of the fistula. Sphincter-preserving procedures such as anal fistula plug and ligation of intersphincteric fistula tract procedure may result in more recurrence requiring repeated operations. The aim of this study was to evaluate and compare the outcomes of treating fistula in Ano utilizing two methods: Fistula plug (Gore Bio-A) and ligation of intersphincteric tract (LIFT). Methods: Fifty four patients (33 males; 21 female, median ages 42 [range 32-47] years) with high anal inter-transphenteric fistula were treated with LIFT and fistula plug procedures from September 2011 until August 2016 by a single surgeon and were retrospectively evaluated. All were followed for a median of 23.9 (range 4-54) months with clinical examination. Twenty one patients underwent fistula plug and 33 patients underwent LIFT procedure (4 patients of the LIFT group underwent LIFT and rectal mucosa advancement flap). The healing rate and complications were evaluated clinically and through telephone calls. Results: The mean operative time for the Plug was 25 ± 17 min and for the LIFT was 40 ± 20 min (p = 0.017) and the mean hospital stay was 2.4 ± 1.1 and 1.9 ± 0.3 (p = 0.01) respectively. The early complications of the plug and LIFT procedures included; anal pain (33.3%, 66.6%, p = 0.13), perianal discharge (77.8%, 91%, p = 0.62), anal pruritus (38.9%, 50.0%, p = 0.71) and bleeding per rectum (16.7%, 33.3%, p = 0.39) respectively. The overall mean follow-up was 20.9 ± 16.8 months, p = 0.68. There was no statistically significant difference between the two groups (21.9 ± 7.5 months, 19.9 ± 16.1 months, p = 0.682). The healing rate was 76.2% (16/21 patients) in the fistula plug group and 81.1% (27/33 patients) in the LIFT group (p = 0.73). Patients who had LIFT procedure and a mucosal advancement flap had 100% healing rate (4 out of 4 patients). No incontinence of stool or feces and no fistula plug expulsion were seen in our patients. The healing time ranged from 1 to 6 months after surgery. There was no post-operative perianal abscess, cellulitis or pain. Conclusions: LIFT and anal plug are safe procedures for patients with primary and recurrent anal fistula. Both techniques showed excellent results in terms of healing and complication rate. None of our patients had incontinence after 5 years follow-up. The best success rate in our patients was seen after LIFT procedure with mucosal advancement flap. Larger and controlled randomized trials are needed for better assessment of treatment options.